Liver sharing and organ procurement organization performance. Issue 3 (23rd February 2015) - Gentry, Sommer E.; Chow, Eric K. H.; Massie, Allan; Luo, Xun; Zaun, David; Snyder, Jon J.; Israni, Ajay K.; Kasiske, Bert; Segev, Dorry L.
Abstract : Whether the liver allocation system shifts organs from better performing organ procurement organizations (OPOs) to poorer performing OPOs has been debated for many years. Models of OPO performance from the Scientific Registry of Transplant Recipients make it possible to study this question in a data‐driven manner. We investigated whether each OPO's net liver import was correlated with 2 performance metrics [observed to expected (O:E) liver yield and liver donor conversion ratio] as well as 2 alternative explanations [eligible deaths and incident listings above a Model for End‐Stage Liver Disease (MELD) score of 15]. We found no evidence to support the hypothesis that the allocation system transfers livers from better performing OPOs to centers with poorer performing OPOs. Also, having fewer eligible deaths was not associated with a net import. However, having more incident listings was strongly correlated with the net import, both before and after Share 35. Most importantly, the magnitude of the variation in OPO performance was much lower than the variation in demand: although the poorest performing OPOs differed from the best ones by less than 2‐fold in the O:E liver yield, incident listings above a MELD score of 15 varied nearly 14‐fold. Although it is imperative that all OPOs achieve the best possible results, the flow of livers is not explained by OPO performance metrics, and instead, it appears to be strongly related to differences in demand. Liver Transpl 21:293–299, 2015 . © 2015 AASLD.